Antioxidant Activity and Cytotoxicity Against WiDR Cell and Vero Cell of The Karamunting (Rhonomyrtus tomentosa L.) Leaves Ethanol Extract - Marwati Marwati; Andi Anggriani; Asril Burhan; Akbar Awaluddin; Syamsu Nur; Rizky Dharmayanti; Ega Lilingan; Melkisedek D. Tiboyong (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Karamunting (Rhodomyrtus tomentosa L.), a plant used as a traditional medicine, is widely distributed throughout Indonesia. Karamuting has the potential as an antioxidant and anticancer agents because of its phenolic and flavonoid components. This study aimed to determine total phenolic level, antioxidant activity and cytotoxic of karamunting leaves extract. The simplisia of karamunting leaves were extracted by maceration method using 96% ethanol, tested for its antioxidant activity using DPPH and its citotoxic by MTT method (3- (4,5-dimethyltiazol-2-il) -2,5-diphenyl tetrazolium bromide) on WiDr cells and Vero cells. The results of this study showed that the yield of karamunting extract were 15.635% with a total phenolic level of 0.76%, antioxidant activity (IC50 values) of 15,330 μg / mL and cytotoxicity (IC50 values) of 205.7069 μg / mL for WiDr cells and 44.87703 μg / mL for Vero cells. Ethanol extract of karamunting leaves possessed a very strong antioxidant activity while it showed a weak cytotoxic effect on WiDr cells and toxic effect on Vero cells.Keywords: Antioxidant, Anticancer, Karamunting